2022
DOI: 10.21203/rs.3.rs-1952708/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

STOML2 Restricts Mitophagy and Increases Chemosensitivity in Pancreatic Cancer through Stabilizing PARL-induced PINK1 degradation

Abstract: Pancreatic cancer remains one of the most lethal diseases with a relatively low 5-year survival rate, while gemcitabine-based chemoresistance happens constantly. Mitochondria, as the power factory in cancer cells, are involved in the process of chemoresistance. The dynamic balance of mitochondria is under the control of the mitophagy process. Stomatin-like protein 2 (STOML2) locates in the mitochondrial inner membrane and expresses highly in cancer cells. In this study, using a Tissue Microarray (TMA), we foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…STOML2 is involved in maintaining coupled mitochondrial respiration and the formation of respiratory chain complexes [72,73] and has been shown to profoundly alter the metabolic profile and proliferative capacity of cancer cells [74]. Moreover, independent studies have demonstrated an interaction between STOML2 and PINK1 that modulates mitophagy [75,76]. Notably, it has been reported that STOML2 directly interacts with and stabilizes MFN2 and another central fusion gene, OPA1 [60,77].…”
Section: Discussionmentioning
confidence: 99%
“…STOML2 is involved in maintaining coupled mitochondrial respiration and the formation of respiratory chain complexes [72,73] and has been shown to profoundly alter the metabolic profile and proliferative capacity of cancer cells [74]. Moreover, independent studies have demonstrated an interaction between STOML2 and PINK1 that modulates mitophagy [75,76]. Notably, it has been reported that STOML2 directly interacts with and stabilizes MFN2 and another central fusion gene, OPA1 [60,77].…”
Section: Discussionmentioning
confidence: 99%
“…[28] It have been reported that Stomatin-like protein 2 (STOML2), which is located in the mitochondrial inner membrane, too, is highly expressed in cancer cells and correlated with higher survival of patients with PAAD, stabilized PARL and prevented gemcitabine-induced mitophagy and reduced the chemoresistance in pancreatic cancer. [29] Correspondingly, PLD6, also known as phospholipase D6, plays pivotal roles in mitochondrial dynamics. [30] In tumor, PLD6 alters mitochondrial fusion and fission dynamics downstream of myelocytomatosis oncogene, which activates AMPK and inhibits YAP/TAZ in breast cancer, [30] piRNA pathway genes PLD6 also play roles in clear cell renal cell carcinoma and ovarian cancer.…”
Section: Tablementioning
confidence: 99%
“…Essential role in mitochondrial quality control by mediating mitochondrial clearance by transducing hypoxia signals [107] Presenilin-associated rhomboid-like protein (PARL) Regulator of PINK1 and Parkin [108]…”
Section: Role In Mitophagy Referencesmentioning
confidence: 99%